Effect of liming on the value of magnesium sulphate and two dolomitic limestones as magnesium sources for ryegrass - Jokinen, Raili (Agricultural and Food Science, 1982)
The effect of liming on the fate of magnesium given as either magnesium sulphate (200 mg Mg/3.9kg of soil) or two dolomitic limestones (1140 mg or 1320 mg Mg) in the soil and the values of these three as magnesium sources for ryegrass (Lolium multiflorum) were studied in pot experiment carried out over two growing seasons. The pH(CaCl2) of the very fine sand used as growth base was raised from its initial value of 4.9 to either 5.7 or 6.5 by the addition of calcitic limestone (12 g or 24 g limestone/3.9 kg of soil, respectively). The magnesium sources were compared at these three levels of soil acidity. At pH(CaCl2) 6.5 about 20 % of the magnesium applied as magnesium sulphate was converted into a form not extractable in 1 M neutral ammonium acetate. This not extractable magnesium appeared to be utilized slowly by ryegrass, which may indicate that magnesium bound in various Al-Mg compounds in limed soil is to some extent available to plants. At pH (CaCl2) 5.7 and 6.5 around 70 % and 85 %, respectively, of the magnesium derived from dolomitic limestones was not extractable in neutral ammonium acetate. The ryegrass was unable to utilize this not extractable magnesium during the two-year experimental period. On an acid soil the dolomitic limestones used were a more effective source of magnesium than magnesium sulphate, though on almost neutral soil there was little difference between the two, despite the large difference in the amount of magnesium applied.